Study of Environmental Isotopes and Hydrochemical Characteristics of Groundwater from Springs at Archaeological Sites in Dompu Regency, West Nusa Tenggara, Indonesia - Satrio Satrio; I Nyoman Rema; Sonny Christophorus Wibisono; Luh Suwita Utami; Nyoman Arisanti; I Gusti Ngurah Jayanti; I Wayan Rupa (Universitas Gadjah Mada, 2024)
The existence of groundwater sources in several springs at archaeological sites in Dompu Regency, West Nusa Tenggara, Indonesia, has been widely used by the surrounding community for various needs. However, from a number of the springs, there are springs whose water discharge has decreased. Meanwhile, from a number of existing springs, there is one spring whose groundwater is used every day even though it tastes a bit brackish. For this reason, it is important to conduct a groundwater study in the area with the aim of knowing the characteristics, preliminary identification of recharge areas and quality of groundwater in the study area through an environmental isotope and hydrochemical. The study was conducted by taking a number of groundwater samples from several archaeological sites in Dompu Regency. The results of environmental isotope and hydrochemical analysis show that there are 2 springs (2 archaeological sites), namely the Riwo and Ncona springs, because these two areas are part of the recharge area, which must be preserved by not clearing forest land. Meanwhile, for the quality of groundwater, of the 5 springs located at the archaeological sites, only the Hodo spring is of “poor quality” with the Na–Cl water type; it is unfit for drinking water.